Using expert judgments to rank 45 latin american business journals - Sergio Olavarrieta (RAE: Revista de Administração de Empresas, 2016)
This article presents the results of a study on the perception of quality of Latin American business journals based on the judgment of relevant experts – senior professors with knowledge of Latin American research and journals. Forty-five journals were included in the study. The highest perceived quality scores were given to Academia (CLADEA – Uniandes), RAE (Fundação Getulio Vargas), and Innovar (Universidad Nacional de Colombia). When perceived quality was weighted by awareness, Academia, LABR-Latin American Business Review (University of San Diego – Coppead), and Innovar had the highest scores. Results complement a recent study by Ruiz-Torres, Penkova, and Villafane (2012) that focused on management journals published in Spanish. Analysis of results suggests that language and branding have an effect on the perception of journal quality. Implications for editors/publishers, tenure, promotion, research grant committees, and authors are provided.